Fulfilling the sacred trust : the UN campaign for international accountability for dependent territories in the era of decolonization - Heiss, Mary Ann, 1961- (Cornell University Press, 2020)
"This book considers the UN campaign to extend the sort of activism that was invested in the Trusteeship System to the dependent territories of the victorious World War II allies" --